Memorial space of small towns in Novosibirsk region in historical dynamics (second half of XIX–XX centuries) - E. I. Krasilnikova; O. A. Gromova (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the overview of the main stages of formation and development of the memorial space of small towns in the Novosibirsk region in the second half of XIX–XX centuries. The contexts of the memory politics that influenced the memorial processes in these towns are revealed. The distinctive specificity of developing memorial space of small towns in comparison with Novosibirsk and other big cities of the region is defined. The research is based on published and unpublished works by local historians and specialists in the protection of monuments. The documentation from museums, the All-Russian Society for the Protection of Monuments of History and Culture and its Novosibirsk branch is used in this article. The result of the research reveals the general specificity of the memorial space of small towns in the Novosibirsk region in the XIX–XX centuries, as well as the peculiarities of its development in the seven historical stages identified by the authors.